The Environment in Central Peru during the 18th century: the studies problem - Carcelén Reluz, Carlos Guillermo (2010)
In order to use historical data for revealing temperature changes in Central Peru during the 18th century, it is necessary to recognize and interpret the cultural, economic and social responses when confronted with marked environmental fluctuations. These caused changes to the farming systems, such as reduced productivity and revenues in all social sectors, particularly among the indigenous communities. Faced with this situation, the urban and rural population of Lima responded in numerous ways, from reorganizing irrigation systems, improved technologies and reduced taxes, to increased devotional Catholic ceremonies and in the indigenous sphere a public resurgence of ancestral cults supposedly eliminated in the 17th century.